A lithium silicate lithium supplement and a preparation method and application thereof

CN123018190APending Publication Date: 2026-10-30HU NAN SHENG RONG KE JI YOU XIAN GONG SI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611501336.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

行业内常通过下调煅烧温度、缩短高温保温时长来缓解晶粒长大趋势,但温度降低易造成锂盐前驱体分解不彻底、碳酸锂残留等问题,保温时间不足又会引发固相转化反应不完全,最终产物物相纯度难以达标,两类调控方式均存在明显的性能取舍短板

Benefits of technology

[0015]与现有技术相比,本发明提供的一个或多个技术方案至少具有以下有益效果之一:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018190A_ABST
    Figure CN123018190A_ABST
Patent Text Reader

Abstract

The application belongs to the field of battery materials, and discloses a lithium orthosilicate lithium supplementing agent and a preparation method and application thereof. 4‑ x Mn x SiO4·δMnO·ηLa2O3, wherein 0
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery materials and relates to a lithium replenishment material, specifically a lithium orthosilicate lithium replenishment agent and its preparation method and application. Background Technology

[0002] Lithium orthosilicate (Li4SiO4) is considered a promising cathode lithium replenishment material due to its high lithium content and good air stability. However, two key technical challenges severely restrict its practical application during solid-state synthesis of Li4SiO4: the first challenge is the formation of the Li8SiO6 impurity phase. When the lithium-silicon ratio is controlled at around 4:1, microscopic inhomogeneities inevitably exist in solid-state mixing, leading to excessive lithium concentrations in local areas, even under lithium-poor conditions (i.e., a lithium-silicon ratio less than 4:1). During the calcination cooling stage (<832°C), the excess Li2O in these lithium-rich micro-regions reacts with the already formed Li4SiO4 to generate Li8SiO6. The delithiation potential of Li8SiO6 is too high (>5V), making it unable to decompose within the conventional battery operating voltage window (<4.5V), which not only reduces the effective capacity of the lithium replenishment agent but may also damage the electrode structure. Existing suppression strategies mainly rely on precise control of the lithium-silicon ratio and rapid cooling, but these passive defense methods require extremely high process precision and cannot fundamentally eliminate the microscopic lithium-rich regions.

[0003] To ensure the full progress of the solid-state reaction and improve the purity of Li4SiO4, the synthesis process requires maintaining a high-temperature environment of 700℃ or above. Under this temperature condition, the atomic diffusion and grain boundary migration rates on the grain surface are significantly accelerated, which can easily lead to excessive grain coarsening and abnormal growth. Increased grain size directly leads to a sharp reduction in the specific surface area of ​​the material, and a significant reduction in the effective contact area between the particles and the electrolyte. This not only weakens the electrochemical reactivity of the lithium replenishment agent itself, but also lengthens the solid-state diffusion distance of lithium ions inside the crystal, slowing down the kinetic reaction rate of the lithium replenishment process. The industry often mitigates the grain growth trend by lowering the calcination temperature and shortening the high-temperature holding time. However, lowering the temperature can easily cause problems such as incomplete decomposition of lithium salt precursors and residual lithium carbonate. Insufficient holding time can lead to incomplete solid-state conversion reaction, making it difficult to meet the purity requirements of the final product. Both control methods have obvious performance trade-offs. Summary of the Invention

[0004] In view of the defects and deficiencies of the existing technology, the present invention provides, firstly, a lithium orthosilicate lithium replenishing agent; secondly, a method for preparing the lithium orthosilicate lithium replenishing agent; and thirdly, a battery.

[0005] In a first aspect, the present invention provides a lithium orthosilicate lithium supplement, comprising a core and a carbon coating layer, wherein the core has the general chemical formula Li. 4-x Mn xSiO4·δMnO·ηLa2O3, where 0 <x≤0.10; The carbon coating layer covers at least a portion of the surface of the core; The carbon coating contains elemental sulfur.

[0006] Preferably, δ is 0.0081 to 0.081 and η is 0.0018 to 0.0106.

[0007] Preferably, the mass of the carbon coating layer is 2% to 10% of the total mass of the lithium orthosilicate lithium supplement.

[0008] Preferably, the elemental sulfur is distributed in the nanopores in one or more small molecule forms of S2, S3, and S4.

[0009] Preferably, the carbon coating layer contains nanopores, and at least a portion of the nanopores contain elemental sulfur.

[0010] Secondly, the present invention provides a method for preparing a lithium orthosilicate lithium supplement, comprising the following steps: Step 1: Ball mill the lithium source, nano-silica, manganese oxide, lanthanum oxide and solvent, then vacuum dry, grind and sieve to obtain precursor powder; Step 2: Heat-treat the precursor powder under an inert atmosphere to obtain the matrix material; Step 3: Ball mill the mixed matrix material and carbon source, and heat treat it under an inert atmosphere to obtain an intermediate product; Step 4: Ball mill the intermediate product and elemental sulfur, and heat-treat it under an inert atmosphere to obtain the lithium orthosilicate lithium supplement.

[0011] Preferably, in step 2, the heat treatment temperature is 700~800℃, the heat treatment time is 6~12h, and the heating rate is 3~5℃ / min.

[0012] Preferably, in step 3, the heat treatment temperature is 600~800℃ and the heat treatment time is 1~4h.

[0013] Preferably, in step 4, the heat treatment includes two stages. The first stage heat treatment temperature is 180~250℃ and the holding time is 1~3h. Then, the temperature is increased to enter the second stage, where the second stage heat treatment temperature is 280~350℃ and the holding time is 3~4h.

[0014] Thirdly, the present invention provides a battery comprising the lithium orthosilicate lithium replenishing agent described in the first aspect or the lithium orthosilicate lithium replenishing agent prepared by the preparation method described in the second aspect.

[0015] Compared with the prior art, one or more technical solutions provided by the present invention have at least one of the following beneficial effects: (1) This invention provides a lithium orthosilicate-based lithium supplement agent synergistically modified by MnO and La2O3. The core function of MnO is as a lithium scavenger, actively consuming local excess lithium and suppressing the formation of Li8SiO6 impurity phase from the source. At the same time, some MnO is also used to scavenge lithium. 2+ Entering the lattice to substitute Li + This process enhances electronic conductivity. La2O3, distributed at grain boundaries, acts as an independent phase to suppress the abnormal growth of Li4SiO4 grains during high-temperature calcination. It also anchors polysulfides and catalyzes their redox conversion during the electrochemical operation phase. Furthermore, the introduction of porous carbon coating from glucose pyrolysis and surface modification with elemental sulfur creates a continuous conductive network through the porous carbon layer, solving the problem of poor matrix conductivity. The porous structure improves electrolyte wetting ability and ion conduction rate, and physically prevents particle agglomeration. Surface sulfur active sites reduce interfacial mass transfer impedance, optimize lithium insertion / extraction kinetics, and stabilize interfacial side reactions. Ultimately, a lithium replenishment product with high phase purity, strong lithium release activity, excellent electrochemical kinetic performance, and outstanding long cycle life of the matching battery cell is obtained.

[0016] (2) During the high-temperature synthesis stage, MnO acts as a lithium scavenger, reacting with the excess Li2O in the system to generate LiMnO2, thereby blocking the generation of harmful impurity phases of Li8SiO6 from the thermodynamic source and improving the process tolerance and purity of the main phase. Attached Figure Description

[0017] Figure 1 The image shows the XRD pattern of the matrix material prepared in Example 1-1; Figure 2 XRD patterns of the matrix materials prepared in Examples 1-1 to 1-3; Figure 3 The XRD patterns of the matrix materials prepared in Comparative Examples 2-1 to 2-6 are shown. Figure 4 XRD patterns of the porous carbon-coated intermediates obtained in step 3 of Examples 1-1 and Comparative Examples 2-1; Figure 5 SEM image of the lithium replenishing agent prepared in Example 1-1; Figure 6 The image shows the SEM image of the lithium supplement prepared in Comparative Example 2-1. Detailed Implementation

[0018] The present invention provides the following specific technical solutions.

[0019] The first aspect includes a core and a carbon coating layer, wherein the core has the general chemical formula Li. 4-x Mn x SiO4·δMnO·ηLa2O3, where 0 <x≤0.10; The carbon coating layer covers at least a portion of the surface of the core; The carbon coating contains elemental sulfur.

[0020] Research has revealed that in lithium orthosilicate-based lithium supplements synergistically modified with MnO and La2O3, the core function of MnO is as a lithium scavenger, actively consuming locally excess lithium and suppressing the formation of the Li8SiO6 impurity phase from the source. Partial MnO... 2+ Entering the lattice to substitute Li + To improve electronic conductivity, some Mn 2+ It exists in the form of manganese oxide; La2O3 acts as an independent phase to inhibit the abnormal growth of Li4SiO4 grains during high-temperature calcination, and anchors polysulfides and catalyzes their redox transformation during the electrochemical operation stage. The two work together to solve the three major problems of impurity phase formation, grain coarsening and polysulfide shuttle, resulting in a high-purity, high-activity and long-cycle-life lithium replenishment product.

[0021] The porous carbon coating layer constructs a continuous conductive network, significantly improving the inherent poor conductivity of the lithium orthosilicate matrix and enhancing the lithium insertion / extraction kinetics of the lithium replenisher. At the same time, it prevents the electrolyte from directly eroding the core active material and alleviates the particle pulverization and disintegration during cycling. The interconnected nanopores inside provide a stable loading space for elemental sulfur, and the physical pores confine the diffusion and loss of soluble lithium polysulfides generated during charging and discharging. It can also buffer the volume stress caused by lithium insertion / extraction. The elemental sulfur loaded in the pores can consume trace amounts of water, HF and other corrosive impurities in the electrolyte through redox reactions in the battery system, reducing the continuous irreversible consumption of active lithium by impurities, helping to improve the first coulombic efficiency and achieving functional modification and efficiency enhancement.

[0022] The lanthanum oxide independent phase dispersed at the grain boundaries of lithium orthosilicate can serve as polar adsorption sites. Through Lewis acid-base coordination and electrostatic interaction between lanthanum ions and polysulfide anions, it strongly chemically anchors lithium polysulfides escaping from the carbon layer pores, making up for the shortcomings of weak physical adsorption and easy desorption of pure carbon materials. This fundamentally inhibits the polysulfide shuttle effect. At the same time, the electrocatalytic activity of rare earth oxides reduces the reaction energy barrier of the stepwise transformation of polysulfides, promotes the reversible and efficient redox reaction of sulfur species, avoids irreversible precipitation and deactivation of active sulfur, and ensures the long-term and stable positive effect of sulfur modification.

[0023] Preferably, δ is 0.0081 to 0.081 and η is 0.0018 to 0.0106.

[0024] δ is the molar stoichiometric coefficient of the free MnO independent phase, and η is the molar stoichiometric coefficient of the free lanthanum oxide La2O3 independent phase.

[0025] In practical applications, based on the mass of the lithium orthosilicate matrix, the mass percentage of MnO is 0.5%~5%, and the mass percentage of La2O3 is 0.5%~3%.

[0026] Research has shown that an appropriate amount of MnO can effectively capture excess lithium sources, suppress the Li8SiO6 impurity phase, and improve conductivity through lattice treatment, without reducing the proportion of active lithium or causing manganese leaching side reactions due to excessive amounts. An appropriate amount of La2O3 is sufficient to refine grains through grain boundary pinning and provide polar sites to anchor polysulfides and catalyze their reversible transformation; however, excessive amounts will block lithium transport channels and dilute the lithium replenishment activity. Within this optimal parameter range, production tolerance is strong, ensuring the phase purity and cycle stability of the lithium replenishment agent.

[0027] Preferably, the mass of the carbon coating layer is 2% to 10% of the total mass of the lithium orthosilicate lithium supplement.

[0028] Research has shown that a carbon coating mass range of 2%–10% achieves optimal synergy between conductivity, structural stability, and high lithium replenishment capacity. Within this range, the carbon layer can form a complete and continuous conductive network, effectively improving the conductivity of the substrate. Simultaneously, it constructs abundant nanopores, stabilizing the loading of elemental sulfur, physically confining polysulfide diffusion, buffering lithium insertion / extraction volume deformation, and preventing electrolyte erosion of the particle core. The appropriate carbon content avoids excessive dilution of the active lithium orthosilicate component, fully preserving the effective lithium capacity of the lithium replenisher, balancing excellent electrochemical kinetics and high lithium replenishment efficiency, and meeting the needs of large-scale preparation.

[0029] Preferably, the elemental sulfur is distributed in the nanopores in one or more small molecule forms of S2, S3, and S4.

[0030] Research has revealed that small-molecule short-chain sulfur compounds S2, S3, and S4, loaded within the nanopores of the carbon coating layer, exhibit faster electrochemical reaction kinetics and stronger redox reversibility compared to conventional cyclic S8 elemental sulfur. The polysulfides generated during charge and discharge are shorter in chain and more easily anchored by La2O3 polar sites at grain boundaries, significantly reducing the polysulfide shuttle effect. Simultaneously, the smaller size of the small-molecule sulfur allows for high-density and uniform filling within the micropores of the carbon layer, fully utilizing the pore space to remove trace amounts of HF, moisture, and other lithium-consuming impurities from the electrolyte. This effectively reduces irreversible lithium loss in the battery and further improves the initial coulombic efficiency and cycle stability of batteries equipped with lithium replenishment agents.

[0031] Secondly, the present invention provides a method for preparing a lithium orthosilicate lithium supplement, comprising the following steps: Step 1: Ball mill the lithium source, nano-silica, manganese oxide, lanthanum oxide and solvent, then vacuum dry, grind and sieve to obtain precursor powder; Step 2: Heat-treat the precursor powder under an inert atmosphere to obtain the matrix material; Step 3: Ball mill the mixed matrix material and carbon source, and heat treat it under an inert atmosphere to obtain an intermediate product; Step 4: Ball mill the intermediate product and elemental sulfur, and heat-treat it under an inert atmosphere to obtain the lithium orthosilicate lithium supplement.

[0032] Research has revealed that the presence of the Li8SiO6 impurity phase in lithium orthosilicate lithium supplements affects the effective capacity of the supplement and may also damage the electrode structure. Based on this, MnO functions as a lithium scavenger in the high-temperature solid-state synthesis stage of step two. When local lithium-rich microregions (i.e., unreacted free Li2O) exist in the system, MnO preferentially reacts with them to generate the intermediate phase LiMnO2 (MnO + Li2O → LiMnO2), consuming the locally excess Li2O and interrupting the thermodynamic pathway for Li2O to further react with the already generated Li4SiO4 to form Li8SiO6.

[0033] Compared to the passive defense of existing technologies, this active removal mechanism offers two significant advantages: First, it greatly improves process tolerance. Even with slight errors in the formulation or localized uneven mixing, MnO can effectively remove excess lithium, making it more suitable for large-scale production. Second, it is more thorough. It directly cuts off the impurity phase formation pathway at the thermodynamic source, rather than merely suppressing the nucleation rate kinetically, resulting in higher reliability of impurity phase suppression.

[0034] Furthermore, La2O3 functions as a grain boundary stabilizer during the high-temperature solid-state synthesis stage in step two. La2O3 does not melt or decompose at high temperatures, exhibiting extremely high chemical and thermal stability. Its large-sized La... 3+ (Ionic radius 1.03 Å) tends to accumulate at the grain boundaries of Li4SiO4 during calcination.

[0035] The main microscopic mechanism of grain growth is grain boundary migration, where large grains grow by engulfing smaller grains. This process requires the continuous movement of grain boundaries. La2O3 particles adhere to the grain boundaries, and for the grain boundaries to move, they must overcome the pinning resistance of the La2O3 particles. This physical barrier effectively counteracts the driving force of grain boundary migration, significantly suppressing abnormal grain growth at high temperatures. Simultaneously, the La2O3 enriched at the grain boundaries plays an additional role in the electrochemical operation: its highly polar surface synergistically adsorbs and anchors polysulfide intermediates generated by sulfur oxidation through S-La and Li-O dual-site adsorption, suppressing the shuttle effect; it also exhibits a catalytic effect on the conversion of polysulfides to the final product, accelerating the reaction process and improving lithium replenishment efficiency and interfacial stability.

[0036] Unlike existing methods that simply rely on lowering the temperature or shortening the time to control grain growth, La2O3 grain boundary pinning is an active inhibition mechanism that directly acts on the microscopic pathway of grain growth. Therefore, this invention can achieve effective control of grain size while ensuring the purity of the Li4SiO4 phase.

[0037] Preferably, in step 1, the lithium source is any one or more of lithium carbonate, lithium oxide, and lithium hydroxide.

[0038] Preferably, in step 1, the molar ratio of Li in the lithium source to Si in the nano-silica is (4.00~4.15):1.

[0039] Preferably, in step 1, based on the theoretically generated Li4SiO4 from lithium source and nano-silica, the amount of manganese oxide added is 0.5wt%~5wt%, and the amount of lanthanum oxide added is 0.5wt%~3wt%.

[0040] Preferably, in step 1, the solvent is any one or two of anhydrous ethanol, acetone, and isopropanol; the liquid-to-solid ratio of the solvent to other solid substances is (0.6~1):1g / mL.

[0041] Preferably, in step 1, the vacuum drying temperature is 80~100℃.

[0042] In actual production, the vacuum drying time is adjusted according to the actual amount of material. If the amount of material to be dried is large, the drying time is extended accordingly; if the amount of material to be dried is small, the drying time is shortened accordingly. Furthermore, the dried material is ground and then sieved through a 400-mesh screen. The particles that pass through the sieve are the precursor powder.

[0043] Preferably, in step 2, the heat treatment temperature is 700~800℃, the heat treatment time is 6~12h, and the heating rate is 3~5℃ / min.

[0044] Research has shown that the above-mentioned optimized heat treatment conditions can ensure the complete solid-phase reaction of the precursor, forming a Li4SiO4 main phase with complete crystallization and excellent purity. This not only ensures that MnO can fully exert its lithium capture function and completely consume excess Li2O to suppress the formation of Li8SiO6 impurity phase, but also allows La2O3 to be stably enriched at the grain boundaries to achieve efficient grain boundary pinning and precise control of grain size, avoiding abnormal grain coarsening and lithium salt volatilization caused by high-temperature overheating. The mild and controllable heating rate and moderate holding time ensure the uniform distribution of Mn and La modified components and the stability of the phase structure, ultimately obtaining a lithium replenishing agent matrix material with suitable crystallinity, controllable defects, high electrochemical activity, and stable structure.

[0045] Preferably, in step 3, the carbon source is any one or more of glucose, sucrose, and chitosan.

[0046] Preferably, in step 3, the mass ratio of the matrix material to the carbon source is 100:(5~15).

[0047] Research has shown that carbonization in an inert atmosphere can form a continuous carbon coating layer with abundant nanopores on the particle surface, completely constructing a conductive network to enhance the electronic conductivity of the matrix. Sufficient porosity allows for stable loading of small-molecule sulfur and physical confinement of polysulfides. Under the aforementioned optimized ratio, the carbon layer obtained through carbonization does not excessively encapsulate the core, hindering lithium-ion insertion / extraction, nor does it significantly dilute the active lithium orthosilicate component due to an excessively high carbon content. While ensuring coating integrity, structural buffering, and side reaction suppression, it maximizes the retention of the effective lithium capacity of the lithium replenishing agent, exhibiting good parameter matching and strong batch-to-batch stability.

[0048] Preferably, in step 3, the heat treatment temperature is 600~800℃ and the heat treatment time is 1~4h.

[0049] Research has shown that under the aforementioned optimized heat treatment conditions, the carbon source can be fully carbonized, and a conductive carbon coating layer with interconnected nanopores can be constructed on the core surface. This ensures that the carbon layer has excellent conductivity and a complete pore structure for loading elemental sulfur and physically bound polysulfides, while avoiding excessive graphitization of the carbon layer at excessively high temperatures, which could lead to pore collapse and closure. At the same time, the shorter holding time can prevent secondary growth of lithium orthosilicate grains and damage to the lattice structure caused by long-term high-temperature heat treatment, thus fully preserving the ion transport advantages brought about by the substrate treatment and modification, and taking into account both the controllability of the coating layer structure and the stability of the core phase.

[0050] Preferably, in step 4, the mass ratio of intermediate product to elemental sulfur is 100:(1~5).

[0051] Research has shown that a feed ratio of 100:(1~5) of intermediate product to elemental sulfur allows small-molecule sulfur to be uniformly filled into the nanopores of the carbon coating layer. Sufficient sulfur components can effectively consume harmful impurities such as water and HF in the electrolyte, reducing irreversible lithium loss. At the same time, the filling amount and pore volume have a high degree of matching. Sulfur species are physically confined by the pores and chemically anchored by La2O3 at the grain boundaries, which fully suppresses polysulfide shuttle side reactions. This ratio will not cause a large amount of sulfur to be released due to excessive sulfur loading exceeding the pore space. It can also avoid the situation where insufficient sulfur content cannot play a role in impurity removal and efficiency enhancement. While improving the first coulombic efficiency of the battery, it will not reduce the proportion of active lithium replenishment matrix and reduce the overall lithium replenishment capacity.

[0052] Preferably, in step 4, the heat treatment includes two stages. The first stage heat treatment temperature is 180~250℃ and the holding time is 1~3h. Then, the temperature is increased to enter the second stage, where the second stage heat treatment temperature is 280~350℃ and the holding time is 3~4h.

[0053] Research has shown that the first-stage heat treatment fully melts sulfur and allows it to penetrate into the micropores inside the carbon coating through capillary action, achieving uniform impregnation and filling. At the same time, the low-temperature inert atmosphere prevents excessive sulfur vaporization and loss, and does not damage the core lithium orthosilicate phase or the porous structure of the carbon layer. The second-stage cooling process allows for slow solidification and shaping, which promotes the stable sealing of sulfur in the pores in the form of small-molecule short chains of S2, S3, and S4. This reduces the formation of easily shuttled long-chain polysulfide precursors, improves redox reversibility, and avoids the negative impact of high temperature on the matrix lattice and the lanthanum oxide pinning structure at the grain boundaries. Ultimately, this achieves pore-confined encapsulation of sulfur and precise control of the configuration of small-molecule sulfur, reducing the risk of polysulfide shuttle in subsequent electrochemical processes from the preparation stage.

[0054] Preferably, in steps 1, 3, and 4, the ball milling speed is independently 300~500 r / min, and the ball milling time is independently 4~8 h.

[0055] Thirdly, the present invention provides a battery comprising the lithium orthosilicate lithium replenishing agent described in the first aspect or the lithium orthosilicate lithium replenishing agent prepared by the preparation method described in the second aspect.

[0056] To make the technical problems, technical solutions and technical advantages of the present invention clearer, a detailed description will be given below with reference to specific examples. However, the scope of protection of the present invention is not limited to the following specific embodiments.

[0057] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.

[0058] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.

[0059] Example 1-1: A method for preparing a lithium orthosilicate lithium supplement includes the following steps: Step 1: Lithium carbonate was selected as the lithium source. The lithium source, nano-silica, manganese oxide, lanthanum oxide and anhydrous ethanol were mixed. The molar ratio of Li in lithium carbonate to Si in nano-silica was 4.06:1. Based on the theoretical mass of Li4SiO4 produced, 2.75wt% manganese oxide and 1.75wt% lanthanum oxide were added. The mixture was ball-milled at 400 r / min for 6 h. After ball milling, it was vacuum dried at 90℃. After drying, it was ground and passed through a 400 mesh sieve to obtain the precursor powder.

[0060] Step 2: The precursor powder was placed in an inert atmosphere (nitrogen atmosphere) and heated to 750℃ at a rate of 4℃ / min, and held at that temperature for 9 hours to obtain the matrix material. The XRD pattern of the matrix material is shown below. Figure 1 As shown, by Figure 1 It can be seen that the matrix material is composed of three phases: Li4SiO4, La2O3 and MnO. The specific composition of the three phases can be determined according to the raw material ratio.

[0061] Step 3: The matrix powder and glucose are ball-milled and mixed at a mass ratio of 100:10. The mixture is then placed in an inert atmosphere (nitrogen atmosphere) and kept at 700°C for 2.5 hours to carbonize and obtain a porous carbon-coated intermediate product.

[0062] Step 4: The intermediate product and elemental sulfur are ball-milled and mixed at a mass ratio of 100:3. The mixture is then placed in an inert atmosphere (nitrogen atmosphere) and kept at 200°C for 2 hours. The temperature is then raised to 300°C and kept at 3.5 hours. After natural cooling, the mixture is ground and sieved to obtain the final lithium orthosilicate lithium supplement.

[0063] Examples 1-2: A method for preparing lithium orthosilicate lithium supplement differs from Example 1 in that: in step 1, the molar ratio of Li in lithium carbonate to Si in nano-silica is 4.00:1. Other parameters and steps 2-4 remain consistent with Example 1-1.

[0064] Examples 1-3: A method for preparing lithium orthosilicate lithium supplement differs from Example 1 in that: in step 1, the molar ratio of Li in lithium carbonate to Si in nano-silica is 4.15:1. Other parameters and steps 2-4 remain consistent with Example 1-1.

[0065] Example 2: A method for preparing a lithium orthosilicate lithium supplement includes the following steps: Step 1: Lithium oxide was selected as the lithium source. The lithium source, nano-silica, manganese oxide, lanthanum oxide and anhydrous ethanol were mixed. The molar ratio of Li in lithium oxide to Si in nano-silica was 4.00:1. Based on the theoretical mass of Li4SiO4 produced, 0.5wt% manganese oxide and 0.5wt% lanthanum oxide were added. The mixture was ball-milled at 300 r / min for 4 h. After ball milling, it was vacuum dried at 80℃. After drying, it was ground and passed through a 400 mesh sieve to obtain the precursor powder.

[0066] Step 2: Place the precursor powder in an inert atmosphere (nitrogen atmosphere), heat it to 700℃ at a heating rate of 3℃ / min, and hold it at that temperature for 6 hours to obtain the matrix material.

[0067] Step 3: The matrix powder and glucose are ball-milled and mixed at a mass ratio of 100:5. The mixture is then placed in an inert atmosphere (nitrogen atmosphere) and kept at 600°C for 1 hour to carbonize and obtain a porous carbon-coated intermediate product.

[0068] Step 4: The intermediate product and elemental sulfur are ball-milled and mixed at a mass ratio of 100:1. The mixture is then placed in an inert atmosphere (nitrogen atmosphere) and kept at 180°C for 1 hour, then heated to 280°C and kept at 280°C for 3 hours. After natural cooling, grinding and sieving are performed to obtain lithium orthosilicate lithium supplement.

[0069] Example 3: A method for preparing a lithium orthosilicate lithium supplement includes the following steps: Step 1: Lithium hydroxide was selected as the lithium source. A mixture of lithium source, nano-silica, manganese oxide, lanthanum oxide and anhydrous ethanol was prepared. The molar ratio of Li in lithium hydroxide to Si in nano-silica was 4.15:1. Based on the theoretical mass of Li4SiO4 produced, 5wt% manganese oxide and 3wt% lanthanum oxide were added. The mixture was ball-milled at 500 r / min for 8 h. After ball milling, it was vacuum-dried at 100℃. After drying, it was ground and passed through a 400-mesh sieve to obtain the precursor powder.

[0070] Step 2: Place the precursor powder in an inert atmosphere (nitrogen atmosphere), heat it to 800℃ at a heating rate of 5℃ / min, and hold it at that temperature for 12h to obtain the matrix material.

[0071] Step 3: The matrix powder and glucose are ball-milled and mixed at a mass ratio of 100:10. The mixture is then placed in an inert atmosphere (nitrogen atmosphere) and kept at 800°C for 4 hours to carbonize and obtain a porous carbon-coated intermediate product.

[0072] Step 4: The intermediate product and elemental sulfur are ball-milled and mixed at a mass ratio of 100:5. The mixture is then placed in an inert atmosphere (nitrogen atmosphere) and kept at 250°C for 1 hour, then heated to 350°C and kept at 350°C for 4 hours. After natural cooling, grinding and sieving are performed to obtain the final lithium orthosilicate lithium supplement.

[0073] Comparative Example 1: A method for preparing a lithium orthosilicate lithium supplement includes the following steps: Step 1: Lithium carbonate was selected as the lithium source. The lithium source, nano-silica and anhydrous ethanol were mixed. The molar ratio of Li in lithium carbonate to Si in nano-silica was 4.06:1. The mixture was ball-milled at 400 r / min for 6 h. After ball milling, it was vacuum dried at 90℃. After drying, it was ground and passed through a 400 mesh sieve to obtain the precursor powder.

[0074] Step 2: Place the precursor powder in an inert atmosphere (nitrogen atmosphere), raise the temperature to 750°C at a rate of 4°C / min, and hold for 9 hours to obtain lithium orthosilicate lithium supplement.

[0075] Comparative Example 2-1: A method for preparing a lithium orthosilicate lithium supplement includes the following steps: Step 1: Lithium carbonate was selected as the lithium source. The lithium source, nano-silica, lanthanum oxide and anhydrous ethanol were mixed. The molar ratio of Li in lithium carbonate to Si in nano-silica was 4.06:1. Based on the theoretical mass of Li4SiO4 produced, 1.75wt% lanthanum oxide was added. The mixture was ball-milled at 400 r / min for 6 h. After ball milling, it was vacuum dried at 90℃. After drying, it was ground and passed through a 400-mesh sieve to obtain the precursor powder.

[0076] Steps 2 through 4 are the same as in Example 1.

[0077] Comparative Example 2-2: A method for preparing a lithium orthosilicate lithium supplement differs from Comparative Example 2-1 in that: In step 23, the molar ratio of Li in lithium carbonate to Si in nano-silica is 4.00:1. Other parameters and steps 2-4 are consistent with Comparative Example 2-1.

[0078] Comparative Examples 2-3: A method for preparing a lithium orthosilicate lithium supplement differs from Comparative Example 2-1 in that: Step 1: The molar ratio of Li in lithium carbonate to Si in nano-silica is 4.03:1. Other parameters and steps 2-4 are consistent with Comparative Example 2-1.

[0079] Comparative Examples 2-4: A method for preparing a lithium orthosilicate lithium supplement differs from Comparative Example 2-1 in that: Step 1: The molar ratio of Li in lithium carbonate to Si in nano-silica is 4.09:1. Other parameters and steps 2-4 are consistent with Comparative Example 2-1.

[0080] Comparative Examples 2-5: A method for preparing a lithium orthosilicate lithium supplement differs from Comparative Example 2-1 in that: Step 1: The molar ratio of Li in lithium carbonate to Si in nano-silica is 4.12:1. Other parameters and steps 2-4 are consistent with Comparative Example 2-1.

[0081] Comparative Examples 2-6: A method for preparing a lithium orthosilicate lithium supplement differs from Comparative Example 2-1 in that: Step 1: The molar ratio of Li in lithium carbonate to Si in nano-silica is 4.15:1. Other parameters and steps 2-4 are consistent with Comparative Example 2-1.

[0082] Comparative Example 3: A method for preparing a lithium orthosilicate lithium supplement includes the following steps: Step 1: Lithium carbonate was selected as the lithium source. The lithium source, nano-silica, manganese oxide and anhydrous ethanol were mixed. The molar ratio of Li in lithium carbonate to Si in nano-silica was 4.06:1. Based on the theoretical mass of Li4SiO4 produced, 2.75wt% manganese oxide was added. The mixture was ball-milled at 400 r / min for 6 h. After ball milling, it was vacuum dried at 90℃. After drying, it was ground and passed through a 400 mesh sieve to obtain the precursor powder.

[0083] Steps 2 through 4 are the same as in Example 1.

[0084] Comparative Example 4: A method for preparing a lithium orthosilicate lithium supplement includes the following steps: Step 1: Lithium carbonate was selected as the lithium source. A mixture of lithium source, nano-silica, manganese oxide, lanthanum oxide and anhydrous ethanol was prepared. The molar ratio of Li in lithium carbonate to Si in nano-silica was 4.06:1. Based on the theoretical mass of Li4SiO4 produced, 2.75wt% manganese oxide and 1.75wt% lanthanum oxide were added. The mixture was ball-milled at 400 r / min for 6 h. After ball milling, it was vacuum dried at 90℃. After drying, it was ground and passed through a 400-mesh sieve to obtain the precursor powder.

[0085] Step 2: Place the precursor powder in an inert atmosphere (nitrogen atmosphere), raise the temperature to 750°C at a rate of 4°C / min, and hold for 9 hours to obtain lithium orthosilicate lithium supplement.

[0086] Comparative Example 5: A method for preparing a lithium orthosilicate lithium supplement includes the following steps: Step 1: Lithium carbonate was selected as the lithium source. A mixture of lithium source, nano-silica, manganese oxide, lanthanum oxide and anhydrous ethanol was prepared. The molar ratio of Li in lithium carbonate to Si in nano-silica was 4.06:1. Based on the theoretical mass of Li4SiO4 produced, 2.75wt% manganese oxide and 1.75wt% lanthanum oxide were added. The mixture was ball-milled at 400 r / min for 6 h. After ball milling, it was vacuum dried at 90℃. After drying, it was ground and passed through a 400-mesh sieve to obtain the precursor powder.

[0087] Step 2: Place the precursor powder in an inert atmosphere (nitrogen atmosphere), heat it to 750℃ at a heating rate of 4℃ / min, and hold it at that temperature for 9 hours to obtain the matrix material.

[0088] Step 3: The matrix powder and glucose are ball-milled and mixed at a mass ratio of 100:10. The mixture is then placed in an inert atmosphere (nitrogen atmosphere) and kept at 700°C for 2.5 hours. After natural cooling, it is ground and sieved to obtain the final lithium orthosilicate lithium supplement.

[0089] Figure 2 The XRD patterns of the matrix materials prepared in Examples 1-1 to 1-3 show that the diffraction peak positions of the products prepared by different lithium-silicon molar ratios are consistent. The main phase corresponds highly to the standard PDF card of lithium orthosilicate. The main phase is high-purity Li4SiO4, and there is no diffraction signal of impurity phase (Li8SiO6).

[0090] Figure 3 The XRD patterns of the matrix materials prepared in Comparative Examples 2-1 to 2-6 are shown. When only lanthanum is added, the uneven mixing of the materials during ball milling can easily cause local imbalance of lithium-silicon ratio, which in turn leads to the precipitation of Li8SiO6 impurity phase. Moreover, the ability to control crystal growth is limited. As the molar ratio of lithium-silicon increases, the risk of the formation of lithium-rich subphase Li8SiO6 increases accordingly. The phase purity is inferior to that of the manganese-lanthanum co-treated example samples.

[0091] Figure 4 The XRD patterns are of the porous carbon-coated intermediate products obtained in step 3 of Examples 1-1 and Comparative Example 2-1. After porous carbon coating heat treatment, the main crystalline phase of the products in Examples 1-1 and Comparative Example 2-1 is Li4SiO4. Glucose pyrolysis forms an amorphous carbon coating layer without any crystalline carbon diffraction peaks. The carbon coating heat treatment process did not destroy the crystalline structure of the lithium orthosilicate matrix. After high-temperature carbon coating treatment, the diffraction signal of the previously generated LiMnO2 intermediate phase completely disappeared, indicating that the manganese component of the LiMnO2 intermediate phase was re-embedded in the Li4SiO4 lattice after solid-state reaction. In Example 1-1, which was co-treated with manganese and lanthanum, not only did not show the lithium-rich Li8SiO6 impurity phase, but all the characteristic diffraction peaks of its Li4SiO4 also shifted to higher angles, originating from the smaller ionic radius of Mn. 2+ Substitution of some Li in the crystal lattice + The shrinkage of the unit cell directly proves that some manganese elements have achieved effective lattice treatment, while some manganese elements exist as independent phases. In contrast, the diffraction peaks of the comparative example 2-1, which only treated with lanthanum and did not introduce MnO, were broadened and the crystal integrity was poor. It was prone to local lithium enrichment and precipitation of trace amounts of Li8SiO6 impurity phase due to uneven material mixing and thermal disturbance during heat treatment. This proves that the co-treatment of manganese and lanthanum can improve the stability of the crystal structure through ion occupancy regulation, effectively suppress the generation of lithium-rich secondary phases, and the phase purity and lattice regularity are significantly better than those of the single lanthanum treatment system.

[0092] The lithium supplements obtained in the various embodiments and comparative examples were used to prepare pure lithium supplement half-cells in the following manner: The lithium supplements prepared in each example and comparative example were mixed with conductive agent SuperP and binder PVDF at a mass ratio of 80:10:10, respectively, and stirred into a uniform slurry using N-methylpyrrolidone (NMP) as solvent. The slurry was coated onto aluminum foil, dried at 80°C for 2 hours and then vacuum-dried at 120°C for 12 hours, and then cut into circular positive electrode sheets with a diameter of 12 mm. Using lithium metal sheets as negative electrodes, Celgard 2500 polypropylene membranes as separators, and a 1 mol / L LiPF6 EC / DMC / EMC solution (volume ratio 1:1:1) as electrolyte, CR2032 coin cells were assembled in an argon glove box and allowed to stand for 8-12 hours before testing.

[0093] The lithium supplements obtained in the various embodiments and comparative examples were used to prepare composite positive electrode half-cells in the following manner: The lithium supplements prepared in each example and comparative example were mixed with lithium iron phosphate (LFP) at a mass ratio of 5:95 to form composite active materials. The same formulations (active material: SuperP: PVDF = 80:10:10) were used for slurry preparation, coating, and assembly of half-cells. Meanwhile, blank control cells were prepared using pure LFP as the active material.

[0094] All electrochemical tests were performed on the Blue Electric test system under constant temperature conditions of 25°C.

[0095] Initial charge-discharge test (capacity and initial coulombic efficiency): Charge at a constant current of 0.05C to 4.5V, then charge at a constant voltage of 4.5V until the current ≤0.01C, let stand for 2 minutes, and discharge at a constant current of 0.1C to 2.0V. Record the initial charge specific capacity Cc and discharge specific capacity Cd, and calculate the initial coulombic efficiency ICE = Cd / Cc × 100%.

[0096] Cyclic performance test: After the first charge and discharge, the composite positive electrode half cell was charged to 4.2V with constant current and constant voltage at 0.2C (cutoff current 0.02C), and then discharged to 2.5V with constant current at 0.2C. The cycle was repeated 200 times, and the discharge specific capacity of each cycle was recorded to calculate the capacity retention rate.

[0097] Table 1 shows the intrinsic capacity test data of the pure half-cell with lithium supplementation; Table 2 shows the test data of the composite cathode half-cell.

[0098] Table 1 Electrochemical performance of pure lithium-ion half-cells Table 2 Electrochemical performance of the positive electrode half-cell As shown in Tables 1 and 2, the lithium replenishing agent material prepared in Example 1 possesses superior initial charge-discharge capacity and coulombic efficiency. Analysis reveals that this is due to the partial presence of Mn... 2+ Li substitution by lattice+ Lattice doping modification is achieved, which broadens the lithium-ion extraction channel. La2O3 is enriched as an independent phase at the grain boundaries, which refines the grains and inhibits abnormal high-temperature growth. The two mechanisms work together to optimize the ion transport dynamics of the matrix. The porous carbon coating layer constructs a conductive network, and sulfur surface modification further reduces the interface impedance, allowing more lithium in the lattice to be activated and extracted during the first charging process. Therefore, the lithium extraction capacity is better than that of the comparative example.

[0099] Comparative Example 1 did not undergo any metal ion lattice treatment, resulting in a dense crystal structure, high resistance to lithium ion migration, and a significant decrease in lithium source activation and release capacity. At the same time, it lacked a carbon conductive coating layer, resulting in poor powder conductivity, severe polarization during charging, and a lithium extraction amount far lower than that of Example 1 with dual treatment and coating modification, which is the lower limit of the performance of the basic blank control group.

[0100] Comparative Example 2-1 shows that single lanthanum ion treatment can slightly optimize the crystal structure and slightly improve the delithiation capacity compared to untreated Comparative Example 1. However, it lacks the Mn ion-assisted lattice distortion and grain boundary pinning effect. Furthermore, as confirmed by XRD above, single La treatment is prone to generating a lithium-rich Li8SiO6 impurity phase due to uneven mixing. The impurity phase lithium is difficult to effectively activate and release. Therefore, the performance is significantly weaker than that of Mn-La co-treated Example 1. The slightly higher initial efficiency is due to the slight fluctuation in reversible lithium intercalation caused by trace impurities, and there is no substantial improvement in performance.

[0101] Comparative Example 3 shows that the single Mn treatment is better than the single La treatment in improving the release of lattice lithium, but it is still not as good as the synergistic effect of the two treatments. The Li extraction capacity is between that of Comparative Example 2-1 and Example 1, which directly proves that the co-treatment of manganese and lanthanum has a synergistic effect. Single element modification cannot achieve the optimal lithium source release capacity.

[0102] Comparative Example 4, without porous carbon conductive coating and sulfur surface modification, shows that lithium orthosilicate itself has extremely poor electronic conductivity and extremely high ohmic polarization during charging. Most of the lattice lithium cannot be electrochemically activated, resulting in a precipitous drop in delithiation capacity. The slightly higher initial efficiency is due to the extremely low total amount of lithium that can be extracted. A small amount of reversible lithium intercalation increases the proportion, but it does not mean that the lithium replenishment effect is better. It is the worst performing sample in this group, directly proving the necessity of carbon coating and sulfur modification for the electrochemical activation of the lithium replenishment agent.

[0103] In Table 1, Comparative Example 4 showed better first-time performance than Example 1-1. The inventors analyzed that this was because the first-time charging capacity and first-time discharging capacity of Comparative Example 4 were extremely low, which caused its first-time performance to fluctuate more due to the influence of other factors. This resulted in the data showing that the first-time performance of Comparative Example 4 was better than that of Example 1-1, but it does not mean that the first-time performance of Comparative Example 4 was better than that of Example 1-1.

[0104] Comparative Example 5 lacks the optimization of interfacial impedance through elemental sulfur surface modification. The side reaction sites on the particle surface are not passivated, resulting in high resistance at the lithium-ion intercalation / deintercalation interface. The lithium release is much lower than that of Example 1, which also underwent sulfur modification. This verifies that sulfur surface modification can further improve the lithium source release efficiency of the lithium replenishment agent.

[0105] Figure 5 The image shows the SEM image of the lithium supplement prepared in Example 1-1. The lithium orthosilicate particles, which are co-treated with manganese and lanthanum and modified by carbon coating and sulfur modification, have an irregular blocky morphology and slight agglomeration. The overall particle size distribution is relatively uniform.

[0106] Figure 6 The image shows a SEM image of the lithium supplement prepared in Comparative Example 2-1. The lithium supplement modified with only lanthanum treatment also exhibits an irregular blocky morphology, with slight agglomeration, but the overall particle size distribution is relatively uniform. (Comparison) Figure 5 and Figure 6 It can be seen that Mn doping has almost no effect on particle morphology.

[0107] The above-described embodiments are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the technical scope of the present invention, based on the technical solution and concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A lithium orthosilicate lithium supplement, characterized in that, It includes a core and a carbon coating layer, wherein the core has the general chemical formula Li. 4-x Mn x SiO4·δMnO·ηLa2O3, where 0 <x≤0.10; The carbon coating layer covers at least a portion of the surface of the core; The carbon coating contains elemental sulfur.

2. The lithium orthosilicate lithium supplement agent as described in claim 1, characterized in that, δ is 0.0081 to 0.081, and η is 0.0018 to 0.0106.

3. The lithium orthosilicate lithium supplement agent as described in claim 1, characterized in that, The mass of the carbon coating layer is 2% to 10% of the total mass of the lithium orthosilicate lithium supplement.

4. The lithium orthosilicate lithium supplement agent as described in claim 1, characterized in that, The sulfur element is any one or more small molecule forms of S2, S3, and S4; The carbon coating layer contains nanopores, and at least a portion of the nanopores contain elemental sulfur.

5. The method for preparing lithium orthosilicate as described in any one of claims 1 to 4, characterized in that, Includes the following steps: Step 1: Ball mill the lithium source, nano-silica, manganese oxide, lanthanum oxide and solvent, then vacuum dry, grind and sieve to obtain precursor powder; Step 2: Heat-treat the precursor powder under an inert atmosphere to obtain the matrix material; Step 3: Ball mill the mixed matrix material and carbon source, and heat treat it under an inert atmosphere to obtain an intermediate product; Step 4: Ball mill the intermediate product and elemental sulfur, and heat-treat it under an inert atmosphere to obtain the lithium orthosilicate lithium supplement.

6. The method for preparing the lithium orthosilicate lithium supplement as described in claim 5, characterized in that, In step 1, the lithium source is any one or more of lithium carbonate, lithium oxide, and lithium hydroxide; The molar ratio of Li in the lithium source to Si in the nano-silica is (4.00~4.15):1; Based on the theoretically generated Li4SiO4 from lithium source and nano-silica, the amount of manganese oxide added is 0.5wt%~5wt%, and the amount of lanthanum oxide added is 0.5wt%~3wt%.

7. The method for preparing lithium orthosilicate supplement as described in claim 5, characterized in that, In step 2, the heat treatment temperature is 700~800℃, the heat treatment time is 6~12h, and the heating rate is 3~5℃ / min.

8. The method for preparing the lithium orthosilicate lithium supplement as described in claim 5, characterized in that, In step 3, the carbon source is any one or more of glucose, sucrose, and chitosan; The mass ratio of matrix material to carbon source is 100: (5~15); The heat treatment temperature is 600~800℃, and the heat treatment time is 1~4h.

9. The method for preparing the lithium orthosilicate lithium supplement as described in claim 5, characterized in that, In step 4, the mass ratio of intermediate product to elemental sulfur is 100:(1~5). The heat treatment consists of two stages. The first stage heat treatment temperature is 180~250℃ and the holding time is 1~3h. The second stage heat treatment temperature is 280~350℃ and the holding time is 3~4h.

10. A battery, characterized in that, The lithium orthosilicate lithium supplement agent includes the lithium orthosilicate lithium supplement agent according to any one of claims 1 to 4 or the lithium orthosilicate lithium supplement agent prepared by the preparation method according to any one of claims 5 to 9.